2018
DOI: 10.1128/microbiolspec.rwr-0024-2018
|View full text |Cite
|
Sign up to set email alerts
|

RNA Localization in Bacteria

Abstract: Diverse mechanisms and functions of post-transcriptional regulation by small regulatory RNAs (sRNAs) and RNA binding proteins (RBPs) have been described in bacteria. In contrast, little is known about the spatial organization of RNAs in bacterial cells. In eukaryotes, subcellular localization and transport of RNAs play important roles in diverse physiological processes, such as embryonic patterning, asymmetric cell division, epithelial polarity, and neuronal plasticity. It is now clear that bacterial RNAs also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 149 publications
(196 reference statements)
2
14
0
Order By: Relevance
“…In order to co-transcriptionally regulate chromosomally encoded targets, sRNAs should be able to diffuse into the nucleoid region, which normally has a higher diffusion barrier. A previous report demonstrated that sRNAs have unbiased distribution between the nucleoid and cytoplasm using a few plasmid-encoded sRNAs as examples (69,70). Here, using single-molecule localization microscopy (SMLM), we confirmed the unbiased localization for these two sRNAs under our experimental conditions (Figure 7).…”
Section: Discussionsupporting
confidence: 85%
“…In order to co-transcriptionally regulate chromosomally encoded targets, sRNAs should be able to diffuse into the nucleoid region, which normally has a higher diffusion barrier. A previous report demonstrated that sRNAs have unbiased distribution between the nucleoid and cytoplasm using a few plasmid-encoded sRNAs as examples (69,70). Here, using single-molecule localization microscopy (SMLM), we confirmed the unbiased localization for these two sRNAs under our experimental conditions (Figure 7).…”
Section: Discussionsupporting
confidence: 85%
“…Subsequently, the brightest spots (top 10%) in the field of view were tracked using the algorithm developed by Sbalazarini and Koumoutsakos (Sbalzarini and Koumoutsakos, 2005). A typical field of view usually contained dozens of cells, a portion of which were not fluorescent while others presented distinct bright speckles, localized at the cell poles as expected from literature (Fei and Sharma, 2018).…”
Section: Methodssupporting
confidence: 61%
“…Diverse examples of transcript-specific mRNA localization have been described across the tree of life ranging from bacteria (Fei and Sharma, 2018) to humans (Khalil et al, 2018). Although early discoveries of localized mRNAs were thought to represent exceptional cases, recent advances in mRNA proximity labeling suggest that mRNA localization may be more widespread than previously thought (Fazal et al, 2019;Taliaferro, 2019).…”
Section: Mrna Localization Is a Widespread Feature Of Cell Biologymentioning
confidence: 99%